Near and intermediate visual and reading performance of patients with a multifocal apodized diffractive intraocular lens using an electronic reading desk - Attia, Mary; Khoramnia, Ramin; Auffarth, Gerd U.; Kirchner, Marietta; Holzer, Mike P. (Journal of cataract and refractive surgery, 2016)
Purpose - To functionally evaluate an apodized diffractive multifocal intraocular lens (IOL) using an electronic reading desk (Salzburg Reading Desk). - Setting - University Eye Clinic Heidelberg, Heidelberg, Germany. - Design - Prospective case series. - Methods - After implantation of an Acrysof IQ Restor +3.0 diopter (D) multifocal IOL, uncorrected (UDVA) and corrected (CDVA) distance visual acuities, uncorrected (UNVA) and distance-corrected (DCNVA) near visual acuities, and uncorrected (UIVA) and distance-corrected (DCIVA) intermediate visual acuities were determined. Criteria for evaluating reading acuity were the reading speed and print size. Monocular and binocular examinations were performed with the electronic reading desk at fixed distances and at the patient's preferred near and intermediate distances. In addition, a subjective questionnaire was administered. - Results - Forty eyes (20 patients) were enrolled. Monocularly, the medians were UDVA, 0.00 logMAR (range 0.26 to −0.14 logMAR); CDVA, −0.08 logMAR (range 0.16 to −0.24 logMAR); 40 cm UNVA, 0.04 logMAR (range 0.24 to −0.10 logMAR); DCNVA, 0.00 logMAR (range 0.18 to −0.22 logMAR); 80 cm UIVA, 0.15 logMAR (range 0.40 to −0.18 logMAR); DCIVA, 0.16 logMAR (range 0.42 to −0.14 logMAR). The monocular reading desk examinations resulted in an uncorrected reading acuity of 0.11 logMAR (range 0.49 to −0.01 logMAR) at 40 cm and 0.30 logMAR (range 0.48 to 0.00 logMAR) at 80 cm. Patients reported a high rate of spectacle independence and satisfaction in everyday life. - Conclusion - The +3.0 D IOL provided good postoperative functional results at far and near and improved the visual and reading acuity at an intermediate distance. - Financial Disclosures - The International Vision Correction Research Centre has received research grants, travel expenses, and lecture fees from various intraocular lens manufacturers. None of the authors has a financial or proprietary interest in any material or method mentioned.